Profil Tingkatan Literasi Lingkungan pada Peserta Didik Tingkat SMP - Estu Putri Maharani; Budiaman; Martini (PT. Penerbit Tiga Mutiara, 2024)
The issue of the environment has become a major concern globally. Environmental literacy plays a crucial role in empowering individuals to address current environmental challenges. To assess the level of environmental literacy among students, this research focused on evaluating the abilities of students at SMP Negeri 158 Jakarta, a school committed to the Adiwiyata program. The study employed a descriptive approach involving 62 eighth-grade students as research subjects. Data were collected through a series of interviews, questionnaires, and tests. Data analysis was conducted using descriptive statistical analysis methods, assessing scores for each environmental literacy indicator. The research findings indicated that the majority of students demonstrated a moderate level of environmental literacy in cognitive indicators, reaching 48%. Meanwhile, the affective indicators showed that the majority of students were in the high category, at 56%. For behavioral indicators, the majority of students were in the moderate category, reaching 76%. The school continues to strive to improve students' environmental literacy as part of efforts to cultivate behaviors that reflect care and awareness for the environment. These actions aim to shape students with a strong and sustainable environmental culture.